Effects of aromatase inhibitors on proliferation and apoptosis in eutopic endometrial cell cultures from patients with endometriosis - Meresman, Gabriela Fabiana (2005)
To study the effect of letrozole (Let) and anastrozole (Anas) on apoptosis and cell proliferation in epithelial endometrial cells (EEC) from patients with endometriosis (EDT). Prospective study. Eighteen women with untreated EDT. Treatment with Let 10 nM and Let 100 nM enhanced values of ApC in cultures from EDT patients. Epithelial endometrial cells treated with Anas 100 nM or Anas 500 nM showed a statistically significant induction on apoptosis levels. Cultures treated with Let 1 nM or Anas 50 nM did not show any significant differences in ApC levels compared with basal conditions. 3H-Thymidine uptake was down regulated by Let 10 nM and Let 100 nM. Similarly, Anas 100 nM and Anas 500 nM showed a significantly lower degree of cell proliferation in EEC. Lower concentrations of Let and Anas did not induce any significant change in cell proliferation rates. Our results show that Let and Anas produced a significant and positive effect on apoptosis and cell proliferation on EEC from EDT patients. These findings support the further investigation of aromatase inhibitors as a treatment option in EDT.